Community Willingness to Participate in A Mosquito Breeding Site Eradication Program: A Study in Bandung, West Java, Indonesia - Faridah, Lia; Nuriyah, Eva; Ekawardhani, Savira; Fauzah, Nisa; Sukandar, Hadyana; Agoes, Ridad (Jurnal Endurance, 2019)
Despite many efforts to prevent dengue, vector control still promising specially through integrated vector management. This effort requires community participation. Therefore, it is crucial to understand the factors that are associated with the willingness of communities in high prevalence areas to participate in mosquito breeding eradication program. This study explored factors associated with the willingness of community members in Bandung to participate in the mosquito breeding eradication program initiated by Indonesian's government, called One House One Larvae Monitor. A community-based cross-sectional study was carried randomly at sub-district level in Bandung from January-November 2018. Interviews using a set of validated questionnaires were conducted to collect data on demography, socioeconomic status, knowledge, attitude and practice regarding implementation of the program. Among 210 participants, the proportion of low-to-middle knowledge, attitude, and practice (KAP) index is more prevalent. Yet, for attaining high-score on KAP, there are three main predictors observed; by being female, at least had attend undergraduate level of education, and being an entrepreneur. A good score in the attitude section does not necessarily translate to good score in the practice section. The results reflect the need for better tools for changing the behavior of society, and it should not be limited to enhancement of society’s knowledge.